Food safety and the effect of fertilizers on human health - Khan , Mahapara; Muhammad Arif; Taleequl Karim; Khan , Duaa; Humera Rashid; Farah Ahmad; Mehwish Zeeshan (International Journal of Endorsing Health Science Research, 2022)
Threats to the environment and the economy significantly worsened human health, greatly outweighing any gains associated with increasing food production. Numerous heavily fertilized crops are used as animal feed, contributing to global food inequalities and unbalanced diets, even in wealthy countries. Hazardous fertilizers have been linked to an excessive burden of communicable and non-communicable diseases, which significantly increase yields and pose considerable environmental and public health risks. The rate at which nitrogen fertilizers are applied is closely related to the buildup of toxins in the surrounding area, groundwater, and leafy and root crops. Consumption of diets including these ingredients has contributed to a significant risk to human health.